2007
DOI: 10.1172/jci31785
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal glucose homeostasis in skeletal muscle–specific PGC-1α knockout mice reveals skeletal muscle–pancreatic β cell crosstalk

Abstract: The transcriptional coactivator PPARγ coactivator 1α (PGC-1α) is a strong activator of mitochondrial biogenesis and oxidative metabolism. While expression of PGC-1α and many of its mitochondrial target genes are decreased in the skeletal muscle of patients with type 2 diabetes, no causal relationship between decreased PGC-1α expression and abnormal glucose metabolism has been established. To address this question, we generated skeletal muscle-specific PGC-1α knockout mice (MKOs), which developed significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
329
6
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 319 publications
(351 citation statements)
references
References 55 publications
13
329
6
3
Order By: Relevance
“…Muscle-derived IL-6, but not IL-8, contributes markedly to systemic levels, where it works in a hormone-like fashion and plays an important role in lipid and glucose metabolism [9,10], principally via activation of AMP-activated protein kinase (AMPK) [10]. Recent studies from others, employing skeletal muscle-specific AKT1 transgenic [11] and muscle-specific peroxisome proliferator activated receptor gamma coactivator 1 alpha (PGC-1α) knockout [12] mice, have also observed altered metabolism in tissues such as pancreas, liver and adipose tissue. The authors of these respective papers hypothesised that musclederived circulatory factors or myokines may have been responsible for the observed tissue cross-talk.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle-derived IL-6, but not IL-8, contributes markedly to systemic levels, where it works in a hormone-like fashion and plays an important role in lipid and glucose metabolism [9,10], principally via activation of AMP-activated protein kinase (AMPK) [10]. Recent studies from others, employing skeletal muscle-specific AKT1 transgenic [11] and muscle-specific peroxisome proliferator activated receptor gamma coactivator 1 alpha (PGC-1α) knockout [12] mice, have also observed altered metabolism in tissues such as pancreas, liver and adipose tissue. The authors of these respective papers hypothesised that musclederived circulatory factors or myokines may have been responsible for the observed tissue cross-talk.…”
Section: Introductionmentioning
confidence: 99%
“…S1). At least in the mTg mice with a reported higher number of oxidative muscle fibers (Handschin, Choi et al., 2007; Lin et al., 2002), this reduction could be based on the exercise‐linked potentiation of the proportion of type IIa and type I muscle fibers, which was not recorded in WT or mKO animals (Figure 2d).…”
Section: Resultsmentioning
confidence: 99%
“…Mice with muscle ablation (mKO) and overexpression (mTg) of PGC‐1α were described previously (Handschin, Choi et al., 2007; Lin et al., 2002). C57/Bl6 wild‐type (WT) mice were obtained from Janvier (Janvier sas, cs 4105, le genest St‐isle f‐53941, St Berthevin Cedex).…”
Section: Methodsmentioning
confidence: 99%
“…Although the effect of IL-6 on insulin release has not been much studied, a few previous publications have found that IL-6 can increase insulin synthesis and secretion [43,44] and even protect the beta cells [45]. In contrast, it was recently reported that IL-6 reduced insulin secretion at low (3.3 mmol/l) but not at high (11.1 mmol/l) glucose concentrations in isolated islets from some animal models [46]. The reason for this discrepancy is currently unclear.…”
Section: Discussionmentioning
confidence: 99%